Clinical andrologists: Do we really need them in the era of ART? - Prashant Motiram Mulawkar; Pankaj N Maheshwari; Sumeet Gopal Agrawal (Wolters Kluwer Medknow Publications, 2021)
Infertility is on a rise, and so is the availability of assisted reproductive technique (ART) centres. The sole aim of these centers is to help these unfortunate couples achieve pregnancy. Hence, the concentration of the treatment is on the female partner, while the male is relegated to just being a source for sperm. In the era of intracytoplasmic sperm injection, when pregnancy is possible even with a single mature sperm, evaluation and management of male factor infertility (MFI) is often neglected. MFI and poor semen parameters are markers of male health. He could be suffering from erectile or ejaculatory issues or with correctable obstructive azoospermia. A simple timely varicocele correction may help resolve the issue. It is important to understand that MFI is not a disease but may be a symptom of major underlying clinical condition like testicular or brain tumors. Infertility treatment could be the only occasion when a male seeks health-care evaluation. India has a large pool of qualified urologists trained in andrological care. In contrast, gynecologists may not be trained in the management of male patients, hence there is an important place for andrological services to be an integral part of ART centers. Andrologists would offer minimal andrological evaluation and condition-specific treatment. This could avoid or reduce the need for invasive and expensive ART. Andrologists could also choose the most appropriate mode of sperm retrieval. Undoubtedly, availability of andrological services would improve the overall quality of care, reduce the costs and complications, and would also be medicolegally safe.